Effect of Retraction on the Lysis of Human Clots with Fibrin Specific and Non-Fibrin Specific Plasminogen Activators - Sabovic, M; Lijnen, H R; Keber, D; Collen, D (Thrombosis and Haemostasis, 1989)
The effect of the serum content of human clots on their sensitivity to lysis with plasminogen activators was studied in a system composed of 125I-fibrin labeled clots immersed in buffer or in citrated plasma. The effect was studied with plasma clots before or after mechanical compression and with whole blood clots before or after retraction, using either the fibrin specific plasminogen activators recombinant tissue-type plasminogen activator (rt-PA) or recombinant single chain urokinase-type plasminogen activator (rscu-PA), and the non-fibrin specific activators recombinant two chain urokinase-type plasminogen activator (rtcu-PA), or streptokinase (SK).In a buffer milieu, all plasminogen activators had a similar fibrinolytic potency towards serum-rich clots (non-compressed plasma clots or non-retracted blood clots): 50% clot lysis in 4 h required 50 to 85 ng plasminogen activator per ml. Serum-poor clots (compressed plasma clots or retracted blood clots) were resistant to lysis in a buffer milieu but became sensitive to lysis following preincubation in plasma for 48 h. These findings indicate that plasma proteins entrapped in clots contribute significantly to their sensitivity to lysis and suggest that the amount of bound or entrapped plasminogen may be a limiting factor. In a plasma milieu, all plasminogen activators lysed serum- rich plasma or blood clots, albeit at higher concentrations (3 to 40 times higher than in the buffer milieu) and with different efficiencies: 50% clot lysis in 4 h required approximately 600 ng/ ml of rtcu-PA but 1,500 to 2,000 ng/ml of rscu-PA. These findings suggest that components of plasma are responsible for increased resistance of clots towards lysis and that the effect is variable for different plasminogen activators. Serum-poor plasma or blood clots were very resistant to lysis with non-fibrin specific agents, but became more sensitive after preincubation in plasma. However, serum-poor plasma or blood clots were sensitive to lysis with fibrin specific plasminogen activators, suggesting that during clot lysis with fibrin specific agents, plasminogen recruited from surrounding plasma may contribute significantly to clot lysis. The concentration of plasminogen activator required to obtain 50% clot lysis in a plasma milieu of compressed plasma clots or retracted blood clots was 390 and 1,600 ng/ml respectively for rt-PA and 1,100 and 3,200 ng/ml respectively for rscu-PA. These data suggest that in a plasma milieu retracted blood clots are more sensitive to lysis with fibrin specific plasminogen activators than with non-fibrin specific agents.
Keywords: Clot retraction; Clot lysis; Plasminogen activators